A new paradigm: innate immune sensing of viruses via the unfolded protein response - Smith, Judith A. (Frontiers in Microbiology, 2014)
The immune system depends upon combinations of signals to mount appropriate responses: pathogen specific signals in the context of co-stimulatory “danger” signals drive immune strength and accuracy. Viral infections trigger anti-viral type I interferon (IFN) responses by stimulating endosomal and cytosolic pattern recognition receptors (PRRs). However, viruses have also evolved many strategies to counteract IFN responses. Are there intracellular danger signals that enhance immune responses to viruses? During infection, viruses place a heavy demand on the protein folding machinery of the host endoplasmic reticulum (ER). To survive ER stress, host cells mount an Unfolded Protein Response (UPR) to decrease ER protein load and enhance protein-folding capacity. Viruses also directly elicit the UPR to enhance their replication. Increasing evidence supports an intersection between the host UPR and inflammation, in particular the production of pro-inflammatory cytokines and type I IFN. The UPR directly activates pro-inflammatory cytokine transcription factors and dramatically enhances cytokine production in response to viral PRR engagement. Additionally, viral PRR engagement may stimulate specific pathways within the UPR to enhance cytokine production. Through these mechanisms, viral detection via the UPR and inflammatory cytokine production are intertwined. Consequently, the UPR response is perfectly poised to act as an infection-triggered “danger” signal. The UPR may serve as an internal “co-stimulatory” signal that 1) provides specificity and 2) critically augments responses to overcome viral subterfuge. Further work is needed to test this hypothesis during viral infections.